2022
DOI: 10.3390/biomedicines10092150
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies as Biomarker and Therapeutic Target in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a rare connective tissue disorder characterized by immune dysregulation evoking the pathophysiological triad of inflammation, fibrosis and vasculopathy. In SSc, several alterations in the B-cell compartment have been described, leading to polyclonal B-cell hyperreactivity, hypergammaglobulinemia and autoantibody production. Autoreactive B cells and autoantibodies promote and maintain pathologic mechanisms. In addition, autoantibodies in SSc are important biomarkers for predicting cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 224 publications
(256 reference statements)
1
33
0
Order By: Relevance
“…Autoantibody profiles in SSc are predictive of disease course and organ involvement. 51 When patients were stratified according to autoantibodies there was a significant increase in copeptin concentration in anti-RNAP III-positive patients. This is in accordance with several observations showing that SSc patients with positive anti-RNAP III antibodies had more frequently rapidly progressive diffuse skin thickening and higher frequency of vascular involvement, such as scleroderma renal crisis, pulmonary hypertension and ischemic damage associated with RP.…”
Section: Discussionmentioning
confidence: 98%
“…Autoantibody profiles in SSc are predictive of disease course and organ involvement. 51 When patients were stratified according to autoantibodies there was a significant increase in copeptin concentration in anti-RNAP III-positive patients. This is in accordance with several observations showing that SSc patients with positive anti-RNAP III antibodies had more frequently rapidly progressive diffuse skin thickening and higher frequency of vascular involvement, such as scleroderma renal crisis, pulmonary hypertension and ischemic damage associated with RP.…”
Section: Discussionmentioning
confidence: 98%
“…It is generally accepted that GPCR autoantibodies are produced against the extracellular regions of the receptor. Depending on the epitope to which they specifically bind, and on their type (monovalent, bivalent), autoantibodies are able to either stimulate or suppress the basal or agonist-stimulated activity of a recognized receptor and, thereby, be involved in the pathogenesis of various diseases [99, [235][236][237]. In this regard, it is interesting that in the case of CXCR3 and CXCR4, patterns of autoantibodies have been identified that are specific not only to extracellular regions, but also to their ICLs.…”
Section: Autoantibodies To Chemokine Receptors Cxcr3 and Cxcr4mentioning
confidence: 99%
“…Endogenous allosteric regulators of PAR1 are autoantibodies produced against its extracellular domains [237,[292][293][294]. A significant proportion of patients with systemic sclerosis have autoantibodies to extracellular regions of PAR1, which are able to activate the receptor, like thrombin, thus acting as allosteric agonists [293].…”
Section: Autoantibodies To Par1mentioning
confidence: 99%
“…The original score was developed in 1979 by Rodnan et al [8]. In summary, these are the two main forms into which SSc can be formally classified at present: 1-limited cutaneous form (lcSSc), characterized by predominantly distal skin thickening and the presence of anticentromere antibodies, and 2-diffuse cutaneous form (dcSSc), in which there are diffuse distal and proximal skin changes associated with the presence of anti-topoisomerase antibodies, anti-RNA-III polymerase antibodies, or other antibodies with antinuclear pattern [9][10][11][12][13][14][19][20][21][22][23][24][25]. The most used biomarkers in SSc are autoantibodies, and in this case, they have utility for diagnosis, classification, and prognosis of the disease; it should also be mentioned that biomarkers can be potential therapeutic targets [4,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%